Toward Resilient, Inclusive and Vital Technological Infrastructures for the Energies of the Landscape - Angelucci, Filippo (Journal of Technology Innovations in Renewable Energy, 2016)
Today, the implementation of energy infrastructure needs a complex â"dialogue" between two apparently different aspects: technical aspects that characterize the processes of production and transformation of energy for the territory, and socio-ecological aspects related to the biological, organizational, and economic variables for cultural, creative, and productive energies of the territory. This new dimension of designing and building the energy infrastructures replaces to the classic esthetical idea of the landscape an integrated vision of human habitat in which innovations play a key role for the redefinition of relationships between téchne, bios and oikos. On these subjects, this article proposes a reflection on a methodological approach to re-think energy infrastructures as technological-environmental interfaces between land resources, energy needs, living dynamics, and inhabiting practices of territories and cities. Four possible scenarios are presented starting from some research experiences developed on Italian Abruzzo region. Through these experiences, emerges a new strategic, tactic and operational framework for the design of energy infrastructures. A new design framework in which energy infrastructures can contribute to re-build relations and connections between the acceptance/correlation of technological innovations and resilience, inclusiveness and vitality of the landscape.